The Toolkit of Success Rate Calculation of Broiler Harvest - Ahmad Sanmorino; Rendra Gustriansyah; Terttiaavini Terttiaavini; Isabella Isabella (Universitas Ahmad Dahlan, 2017)
Failed in the harvest should be avoided by the owners of broiler farms. Various ways are done to make the harvest successful and make a profit. Preparations made before the period of broiler development can be done optimally, with the hope that the harvest is successful. But the problem, on the field in fact not as smooth as had been planned at the beginning or before the development period. There is always a lack or inappropriate so that the harvest is not optimal or even harvest failure. Based on the background that has been described, we tried to create a toolkit that can be used to calculate success rate of the broiler harvest. With this toolkit, broiler farm owners are expected to have a guide and can make the right move in the period of broiler development. To calculate the success rate of broiler harvest, we used a model based on the performance index calculation. Toolkit that created running on local network environment using an Apache web server. The Toolkit uses JavaScript library to display the calculation results in the form of charts that are easier to understand. Based on the results of testing that has been done, this toolkit can perform calculations in a relatively short time. Can present the results of calculations with accurate information. The accuracy of success rate calculation toolkit reached 90%. It is obtained by comparing the performance index and the total weight of broiler that obtained when harvested.